SeasonWatch: Tracking Trees Through the Seasons - Sidhu, Swati; Ramaswami, Geetha (Voices of Teachers and Teacher Educators, 2019)
The paper explains how flora changes during the year and points out that phenology of plants and animals can tell us a lot about our environment. It points out that the phenology (study of cyclic events) of plants also affects the animal phenology. The paper presents data received from volunteers from a survey in a segregated manner from across India.